2009
DOI: 10.1371/journal.pone.0005895
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Virus and Aedes Mosquitoes: Saliva Is Infectious as soon as Two Days after Oral Infection

Abstract: Background Aedes aegypti and Aedes albopictus are potential vectors of chikungunya virus (CHIKV). The recent CHIKV outbreaks were caused by a new variant characterized by a mutation in the E1 glycoprotein gene (E1-226V) which has favored a better transmissibility by Ae. albopictus. As Ae. albopictus tends to replace Ae. aegypti in many regions, one question remained: is Ae. albopictus as efficient as Ae. aegypti to transmit the variant E1-226V of CHIKV?Methodology and FindingsWe infected orally both species wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
285
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(301 citation statements)
references
References 26 publications
13
285
0
3
Order By: Relevance
“…This early dissemination, as well as early transmission potential, has been observed in previous studies. 36,37 The infection rates we observed were relatively low in all of the Ae. aegypti populations we tested compared with populations from other geographic regions.…”
Section: Discussionmentioning
confidence: 70%
“…This early dissemination, as well as early transmission potential, has been observed in previous studies. 36,37 The infection rates we observed were relatively low in all of the Ae. aegypti populations we tested compared with populations from other geographic regions.…”
Section: Discussionmentioning
confidence: 70%
“…The reported correlation between dose and disease severity (more severe at a higher dose) is interesting and may explain, at least in part, the range of symptoms observed in humans. The doses used by the authors are within ranges likely delivered by mosquitoes (24). It would have been interesting if some primates had been challenged by CHIKV-infected mosquitoes, given the increasing evidence that chikungunya fever has an immunological component.…”
Section: Primate Models Of Chikvmentioning
confidence: 96%
“…27 Aedes albopictus mosquitoes can transmit CHIKV within two days of biting a viremic host, and once infected, the mosquito is able to transmit the arbovirus for life. 7 Because this species is an aggressive biter and can take four blood meals during its life span at 20°C, 27 conditions in Auckland would be ideal for a CHIKV outbreak. In addition, it has been previously established that this area of the country could be receptive to dengue.…”
Section: Culex Quinquefasciatusmentioning
confidence: 99%
“…albopictus mosquitoes resulting in improved viral replication and transmission efficiency. [7][8][9] It was shown that a single mutation can increase the range of vectors and hosts of this virus, resulting in greater geographic distribution and establishment in new areas. 9 In 2007, Italy registered the first CHIKV outbreak autochthonously transmitted in Europe.…”
Section: Introductionmentioning
confidence: 99%